Initial and in-service training of Schools Principals:Regulatory Evoution and Institutions - Sánchez Ramón, Juan Miguel (Avances en Supervisión Educativa, 2024)
This essay reviews the evolution of the director and his training. It begins with the dilemma between whether training is a necessity for every manager or if, on the contrary, it is a work, social or personal obligation, essential for the school manager to be truly considered a key factor in the educational system. After this reflection, he delves into the prototype of director that has existed and exists in Spain from the end of the Franco period to the present, comparing and observing the evolutions or changes that the management model has undergone, its functions, its form of access and the both initial and ongoing training received. All of this, framed from the prism of the large number of educational laws published in the period studied and the centers and institutions that are dedicated to the training of the director, always the director, since little work has been done on the training of the management team. as the executive governing body of educational centers. Finally, after looking at some initiatives in the training of directors, we dare to propose a prospective vision of the training of management teams.
Keywords: Teachers center; director; management team; initial training; permanent training